(untitled) (Journal of Engineering, 2016)
Test results of nine reinforced concrete one way slab with and without lacing reinforcement are reported. The tests were designed to study the effect of the lacing reinforcement on the flexural response of one way slabs. The test parameters were considered is the lacing steel ratios of (0, 0.0025, 0.0045, and 0.0065), flexural steel ratios of (0.0025, 0.0045, and 0.0065) and span to the effective depth ratios of (11, 13, and 16). Two specimens had no lacing reinforcement and the remaining seven specimens had the lacing reinforcement. Four point bending test were carried out, one of the specimens was tested under the static load applied gradually up to failure and the other specimens were tested under repeated load (5 cycles) loading-unloading to 80% of the ultimate load of the control specimen then loaded manually by the hydraulic jack up to failure. The specimens showed an improving in ultimate load capacity ranged between (54.54% - 100%) as a result of increasing the lacing steel ratio to (0.0065) and decreasing the span to effective depth ratio by 31.25% respectively with respect to the control specimen. Additionally the using of lacing steel reinforcement leads to reducing the residual deflection by about (57.24%) for the specimen with the largest lacing reinforcement compared with the control specimen (without lacing reinforcement).